بلاک ارکتوراسپاینا برای تخلیه هماتوم ستون فقرات : گزارش یک مورد - asgari, sogol (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2026)
مقدمه: مدیریت بیهوشی در بیماران پرخطر قلبی که نیازمند جراحی اورژانسی ستون فقرات هستند، چالش‌برانگیز است. بلاک ارکتور اسپاینا (ESPB) به‌عنوان یک روش بی‌حسی منطقه‌ای جدید، پتانسیل کاهش نیاز به بیهوشی عمومی و عوارض همودینامیک را دارد. شرح مورد: بیمارآقای ۶۴ ساله با سابقه بیماری قلبی و ترومبوآمبولی ریوی (PTE) تحت درمان آنتی‌کواگولان، دو هفته پس از فیوژن خلفی چهارسطحی ستون فقرات، به علت هماتوم محل جراحی نیازمند تخلیه اورژانسی شد. مشاوره قلب پیش‌تر انجام شده و توصیه به انجام جراحی در مرکز مجهز به کت‌لب و اتاق عمل قلبی داده شده بود. با توجه به فوریت وضعیت، جراحی در مرکز فعلی و تحت بلاک دوطرفه ESPB با هدایت سونوگرافی و سدیشن با دکسمدتومیدین انجام شد. روند جراحی و پس از عمل بدون عارضه گذشت. نتیجه‌گیری: ESPB می‌تواند در بیماران پرخطر جایگزین مناسبی برای بیهوشی عمومی در جراحی‌های اورژانسی ستون فقرات باشد. Background: Anesthetic management in patients with high-risk cardiac diseases who are candidates for emergency spinal surgeries is always challenging. The Erector Spinae Plane Block (ESPB), as a novel technique in regional anesthesia, possesses high potential in reducing the need for general anesthesia and preventing its associated hemodynamic complications. Case Presentation: The patient was a 64-year-old male, a known case of ischemic heart disease and a history of pulmonary thromboembolism (PTE), undergoing treatment with anticoagulant medications. Two weeks following posterior spinal fusion surgery (at four levels), he presented with progressive neurological symptoms caused by a surgical site hematoma and became a candidate for emergency hematoma evacuation. In prior evaluations, cardiology consultation, considering the high risk, had authorized any surgical intervention solely in a center equipped with angiography facilities (Cath Lab) and cardiac surgery. However, due to the urgency of spinal cord compression and the impossibility of transfer, surgery was performed at the current center. To avoid the risks of general anesthesia, the patient underwent bilateral ESPB under ultrasound guidance with sedation using dexmedetomidine. The surgical process and the postoperative period passed without any hemodynamic or respiratory complications. Conclusion: The ESPB technique can be a safe and efficient alternative to general anesthesia in high-risk cardiac patients undergoing spinal surgeries (particularly in emergency cases and where neuraxial anesthesia is contraindicated), which, while providing optimal analgesia, maintains the patient's cardiovascular stability.